2019
DOI: 10.1016/j.chemosphere.2018.12.047
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of aquatic life criteria for four phthalate esters and their ecological risk assessment in Liao River

Abstract: As a critical family of endocrine disruptors, phthalate esters (PAEs) attracted considerable attentions due to increasingly detected worldwide. Aquatic life criteria (ALC) for PAEs are crucial for their accurate ecological risk assessment (ERA) and have seldom been derived before. Given this concern, the purpose of the present study is to optimize the ALCs of four priority PAEs to estimate their ecological risks in Liao River. Reproductive endpoint was found to be more sensitive than other endpoints. Thus, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…The toxicity values of carbamazepine varied from 0.91 to 100,000 μg/L, with the mean concentration of 3201 μg/L, and the most and least sensitive specie was Gobiocypris rarus and Raphidocelis subcapitata , respectively [ 40 , 41 ]. In this study, the most used extrapolation model based on Log-logistic was used to construct the SSD curves of carbamazepine [ 42 , 43 , 44 ] ( Figure 3 ). The HC 5 was calculated to be 36.8 ng/L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity values of carbamazepine varied from 0.91 to 100,000 μg/L, with the mean concentration of 3201 μg/L, and the most and least sensitive specie was Gobiocypris rarus and Raphidocelis subcapitata , respectively [ 40 , 41 ]. In this study, the most used extrapolation model based on Log-logistic was used to construct the SSD curves of carbamazepine [ 42 , 43 , 44 ] ( Figure 3 ). The HC 5 was calculated to be 36.8 ng/L.…”
Section: Resultsmentioning
confidence: 99%
“…Probabilistic risk assessment methods including MOS 10 and JPC are developed on the basis of qualitative risk assessment methods, which make full use of all pollutant toxicity data and environmental monitoring data and take into account the effects of other factors on aquatic biosafety, such as the concentration distribution of pollutants, the total amount of pollutants, the type of aquatic organisms, as well as species’ susceptibility to contaminants. For the convenience of environmental management, experts and scholars have suggested the use of qualitative and quantitative risk-assessment methods to assess the ecological risk of pollutants [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be indicated that Zn, As, Pb and Cr come from the same pollution source, and the Hg, Cd and Cu come from the same pollution source, which demonstrated Cd is usually related to specific steel production processes 31,32 . Zn, Cd, Hg and Pb are enormously affected by anthropogenic source such as mining, smelting and other industrial activities 31,32,33,34 . The component 2 explains 24.8% of all the data variation demonstrating strong loadings with Ni, while the component 3 with 17.7% of all the data variation indicating strong loadings with Hg.…”
Section: Resultsmentioning
confidence: 96%
“…31,32 Zn, Cd, Hg and Pb are enormously affected by anthropogenic source such as mining, smelting and other industrial activities. 31,32,33,34 The component 2 explains 24.8% of all the data variation demonstrating strong loadings with Ni, while the component 3 with 17.7% of all the data variation indicating strong loadings with Hg.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Study on water quality criteria is a new research hotspot in China in recent years [35][36][37][38][39]. Based on the sensitivity of Chinese freshwater organisms to ammonia nitrogen, we have proposed China's ammonia nitrogen ALC function in the previous study [31].…”
Section: Chinese Water Quality Criteria Of Ammonia Nitrogenmentioning
confidence: 99%